Flexible thin-film GaAs solar cells with rear micro-pattern - Jang, Yujeong; Yun, Yeojun; Moon, Sunghyun; Lee, Minhyung; Lee, Jaejin (Journal of the Korean Physical Society, 2021)
Current thin-film GaAs solar cells have a planar resar ohmic contact structure, which might be related to losses due to the photon absorption in the highly doped contact layer. Reducing the rear contact ratio can improve photon absorption through the enhanced back reflection. In this study, by etching the rear p-GaAs contact layer with metal-assisted chemical etching, the micropillar structures consisting of square patterns were formed on the GaAs solar cells, which led to improved reflection and the cell performance. We compared the current density, reflectance, and external quantum efficiency of the solar cells according to the pattern size. The power conversion efficiency was improved from 10.67 to 11.21% for the GaAs single-junction solar cell as compared to that with a planar surface under AM 1.5G illumination.
Keywords: GaAs; Metal-assisted chemical etching; Photon recycling; Rear pattern; Thin-film solar cell